1996
DOI: 10.1021/js950534b
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Applications of Cyclodextrins. 1. Drug Solubilization and Stabilization

Abstract: Cyclodextrins are cyclic oligosaccharides which have recently been recognized as useful pharmaceutical excipients. The molecular structure of these glucose derivatives, which approximates a truncated cone or torus, generates a hydrophilic exterior surface and a nonpolar cavity interior. As such, cyclodextrins can interact with appropriately sized molecules to result in the formation of inclusion complexes. These noncovalent complexes offer a variety of physicochemical advantages over the unmanipulated drugs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
1,069
0
23

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,987 publications
(1,101 citation statements)
references
References 78 publications
9
1,069
0
23
Order By: Relevance
“…However, due to various reasons including cost, toxicology and dosage, the amount of CD that can be used in most formulations should be restricted [6]. Therefore, different methods have been undertaken to improve their performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to various reasons including cost, toxicology and dosage, the amount of CD that can be used in most formulations should be restricted [6]. Therefore, different methods have been undertaken to improve their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different methods have been undertaken to improve their performance. Among the possible different approaches, recent works showed that the addition of suitable auxiliary substances can significantly increase the CD solubilising and complexing abilities by multicomponent complex formation [6]. For instance, it has been shown that the addition of hydroxy-or amino-acids can lead to the improvement of CD performance, which can be seen as a result of the combined effects of salt formation and inclusion complexation [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…CDs interact with poorly water-soluble compounds to increase their apparent solubility. The most prominent mechanism by which this solubilization occurs is the inclusion complex formation in which the guest and host molecules are in dynamic equilibrium with the complex [12]. The kinetics of complexation between NFOH and DM-β-CD was determined, and it was observed that the complexation equilibrium in aqueous solution was reached up to 20 h (data not shown).…”
Section: Kinetics Of Complexation and Phase Solubility Studiesmentioning
confidence: 99%
“…The K a determination between the drug and CD is based on the measurement of an index of changes in physical-chemical properties of a compound upon inclusion. Most methods for determining the K a values are based on the analysis of the concentration dependencies, at titration experiments with the drug molecule and CD [12]. Thus, an important pharmaceutical application of CD is to enhance drug solubility in aqueous solution.…”
Section: Kinetics Of Complexation and Phase Solubility Studiesmentioning
confidence: 99%
“…4) The cyclic oligosaccharide has a hydrophobic cavity in the center of the structure. Guest molecules of suitable size can enter the cavity, and the formation of the inclusion complex is used for stabilizing labile materials, 5) masking odors, 6) and modifying viscosity. 7) Côté and co-workers first reported that a cyclic tetrasaccharide consisting of -D-glucose, cyclo-…”
mentioning
confidence: 99%